2021
DOI: 10.3389/fonc.2021.671474
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Survival of AJCC 8th Stage II Gastric Cancer Patients After D2 Gastrectomy

Abstract: The association between the risk factors and long-term prognosis in patients with stage II gastric cancer after radical gastrectomy has been fully revealed. The purpose of this study was to investigate the independent risk factors for treatment failure in stage II gastric cancer. Demographic, clinical, and pathological information of 247 stage II gastric cancer patients who underwent radical D2 gastrectomy in our department between January 2011 and December 2014 were collected and retrospectively analyzed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…We demonstrated the degree of surgical training to be independent of recurrence rates within our observation period. This observation is consistent with previous reports by other investigators [24][25][26]. As our two patient groups had a similar distribution regarding patient characteristics and tumor stage, surgical quality, as measured by comparable and postoperative morbidity and mortality, may have contributed to equal survival curves in our study.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated the degree of surgical training to be independent of recurrence rates within our observation period. This observation is consistent with previous reports by other investigators [24][25][26]. As our two patient groups had a similar distribution regarding patient characteristics and tumor stage, surgical quality, as measured by comparable and postoperative morbidity and mortality, may have contributed to equal survival curves in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Another study also reported that the presence of PNI is an independent risk prognostic factor of DFS and cancer-specific survival of stage II/III GC [ 25 ]. For stage II GC after radical gastrectomy, PNI showed a predictive value for recurrence [ 26 ]. Similar with the literature, our results showed that the presence of PNI had a higher risk of recurrence and shorter OS in the patients with stage II GC.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zheng et al . reported that AC is not a prognostic factor for stage II GC [ 26 ]. PNI has been shown to be a valuable prognostic factor, so whether PNI can serve as a biomarker to assist decision-making for AC in stage II GC is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival (OS) was defined as the duration between the date of surgery and the date of the final follow-up or death and was used as the primary endpoint[ 8 ]. DSS is defined as the time between the date of operation and the date of all-cause death as the secondary endpoint [ 9 ].…”
Section: Methodsmentioning
confidence: 99%